Assessment of Flood Risk in the Eastern Part of Jamuna Floodplain (Journal of the Asiatic Society of Bangladesh, Science, 2018)
Risk assessment provides the scope to understand the vulnerability situation of any area based on different hazard context. The study has been conducted in the eastern part of Jamuna floodplain area to examine its flood vulnerability. To perform the analysis, the whole study area has been surveyed and examined applying Geographic Information System. The entire hazard, vulnerability as well as the capacity factors are assessed and have been classified into different categories from very low to very high. Individual factor analysis has been considered to realize the specific condition of different factors. Finally, flood hazard map has been prepared to examine the vulnerability of the proposed area. This type of work helps the planners and disaster managers to identify the most risk zone which should receive immediate hazard mitigation measures as well as help to take a decision in an emergency situation when a flood may occur in the study area.Asiat. Soc. Bangladesh, Sci. 44(2): 211-224, December 2018